2022
DOI: 10.1371/journal.pone.0267896
|View full text |Cite
|
Sign up to set email alerts
|

Did you even see that? visual sensory processing of single stimuli under different locomotor loads

Abstract: Modern living and working environments are more and more interspersed with the concurrent execution of locomotion and sensory processing, most often in the visual domain. Many job profiles involve the presentation of visual information while walking, for example in warehouse logistics work, where a worker has to manage walking to the correct aisle to pick up a package while being presented with visual information over data-glasses concerning the next order. Similar use-cases can be found in manufacturing jobs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Additionally, event-related lateralizations (ERLs: the difference between contralateral and ipsilateral activations depending on the spatial code of a stimulus) of the EEG may serve as a marker for the spatial orienting of attention. Previous laboratory research showed that ERLs, such as increases in lateralized N1 amplitude or suppression in lateralized brain oscillatory alpha activity, could give insights into the shift of covert attention in a visual scenery [ 20 ], even in mobile situations [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, event-related lateralizations (ERLs: the difference between contralateral and ipsilateral activations depending on the spatial code of a stimulus) of the EEG may serve as a marker for the spatial orienting of attention. Previous laboratory research showed that ERLs, such as increases in lateralized N1 amplitude or suppression in lateralized brain oscillatory alpha activity, could give insights into the shift of covert attention in a visual scenery [ 20 ], even in mobile situations [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous laboratory research showed that ERLs, such as increases in lateralized N1 amplitude or suppression in lateralized brain oscillatory alpha activity, could give insights into the shift of covert attention in a visual scenery (Foster et al, 2017), even in mobile situations (Reiser et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The MVPA exhibits high sensitivity to subtle changes in neural activity patterns that are difficult to detect through traditional univariate approaches [16], [17]. The primary method used to assess the temporal characteristics of visual Decoding Eye Blink and Related EEG Activity in Realistic Working Environments information perception is the analysis of event-related potentials (ERPs) [18]. However, the limitations of univariate ERPs are their restricted sensitivity to local neural processes and the inability to capture the contributions of multiple neural processes that occur in distributed brain regions involved in visual processing.…”
Section: Introductionmentioning
confidence: 99%